Magnetoelectric and transport properties of (GaMn)Sb thin films: A ferrimagnetic phase in dilute alloys (2017)
We studied the electrical, magnetic, and transport properties of (GaMn)Sb thin films fabricated by the direct current magnetron co-sputtering method. Using X-ray powder diffraction measurements, we identified the presence of ferrimagnetic (Mn 2 Sb) and ferromagnetic (Mn 2 Sb 2 ) phases within the films. We also measured the magnetization of the films versus an applied magnetic field as well as their hysteresis curves at room temperature. We determined the electrical and transport properties of the films through temperature-dependent resistivity measurements using the Van Der Pauw method. The main contribution to the transport process was variable range hopping. Hopping parameters were calculated using percolation theory and refined using the diffusional model. In addition, we determined that all samples had p type semiconductor behavior, that there was an increase in the density of localized states near the Fermi level, and that the binary magnetic phases influenced the electrical properties and transport mechanisms. © 2016 Elsevier B.V.